LEPREL1-RELATED GIANT RETINAL TEAR DETACHMENTS MIMIC THE PHENOTYPE OF OCULAR STICKLER SYNDROME. Issue 3 (March 2023) - Magliyah, Moustafa S.; Almarek, Faisal; Nowilaty, Sawsan R.; Al-Abdi, Lama; Alkuraya, Fowzan S.; Alowain, Mohammed; Schatz, Patrik; Alfaadhel, Talal; Khan, Arif O.; Alsulaiman, Sulaiman M.
Abstract : Supplemental Digital Content is Available in the Text. Biallelic LEPREL1 pathogenic variants can lead to an early-onset rhegmatogenous retinal detachment associated with giant retinal tear. This phenotype resembles and may be confused with that of ocular Stickler syndrome. Abstract : Purpose: To describe the features of retinal detachments and high myopia in patients with novel pathogenic variants in LEPREL1 and report a possible association with nephropathy. Methods: Retrospective study of 10 children with biallelic LEPREL1 pathogenic variants. Data included ophthalmic features, surgical interventions, and genetic and laboratory findings. Results: 10 patients (8 females) from three families with homozygous (2) or compound heterozygous (1) variants in LEPREL1 were included. At presentation, mean age was 9.9 ± 2.6 years. Mean axial length was 28.9 ± 1.9 mm and mean refraction was −13.9 ± 2.8 diopters. Bilateral posterior subcapsular cataracts were present in eight patients (80%), with lens subluxation in five eyes of three patients (30%). Rhegmatogenous retinal detachments (RRD), associated with giant retinal tears (GRT), developed in seven eyes of five patients (50%) at a mean age of 14.14 ± 5.9 years. Six were successfully reattached with mean Snellen best-corrected visual acuity improving from 20/120 preoperatively to 20/60 at last follow-up. Urinalysis in nine patients revealed microhematuria and/or mild proteinuria in six patients (67%). Conclusion: LEPREL1 -related high myopia confers a high risk of early-onset GRT-related RRD. The ocular phenotype may be confused with that of ocular Stickler syndrome if genetic testing is not performed. Further investigations into a potential association with renal dysfunction are warranted.